2009
DOI: 10.5194/acp-9-831-2009
|View full text |Cite
|
Sign up to set email alerts
|

A global stratospheric bromine monoxide climatology based on the BASCOE chemical transport model

Abstract: Abstract.A new climatology of stratospheric BrO profiles based on a parameterization using dynamical and chemical indicators has been developed, with the aim to apply it to the retrieval of tropospheric BrO columns from space nadir measurements. The adopted parameterization is based on three years of output data from the 3-D chemistry transport model BASCOE. The impact of the atmospheric dynamics on the stratospheric BrO distribution is treated by means of Br y /ozone correlations built from 3-D-CTM model resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 72 publications
8
85
1
Order By: Relevance
“…Recently it has been shown by Theys et al (2009) that some enhancement in total BrO column can be caused by increases in stratospheric BrO due to a decrease in tropopause height coincident with low surface pressure. For the cases we have discussed here, tropospheric BrO columns (derived using climatological data validated using ground-based balloon and satellite limb stratospheric BrO observations) indicate the same structure of BrO enhancements that are evident in the total column, with tropospheric column amounts up to 8×10 13 molec/cm 2 (N. Theys personal communication, 2010).…”
Section: Expanding the Low Pressure System/bro Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown by Theys et al (2009) that some enhancement in total BrO column can be caused by increases in stratospheric BrO due to a decrease in tropopause height coincident with low surface pressure. For the cases we have discussed here, tropospheric BrO columns (derived using climatological data validated using ground-based balloon and satellite limb stratospheric BrO observations) indicate the same structure of BrO enhancements that are evident in the total column, with tropospheric column amounts up to 8×10 13 molec/cm 2 (N. Theys personal communication, 2010).…”
Section: Expanding the Low Pressure System/bro Linkmentioning
confidence: 99%
“…For the cases we have discussed here, tropospheric BrO columns (derived using climatological data validated using ground-based balloon and satellite limb stratospheric BrO observations) indicate the same structure of BrO enhancements that are evident in the total column, with tropospheric column amounts up to 8×10 13 molec/cm 2 (N. Theys personal communication, 2010). Given that calculated stratospheric columns at southern high latitudes range from 2.5 to 4.5×10 13 molec/cm 2 (Theys et al, 2009), the BrO hotspots shown in the BrO total column cannot be attributed to the stratosphere and must arise from a tropospheric source.…”
Section: Expanding the Low Pressure System/bro Linkmentioning
confidence: 99%
“…Theys et al (2011) fitted total slant columns of BrO to the solar backscattered radiation spectra. They then removed the stratospheric contribution by using correlations of stratospheric BrO with ozone and NO 2 from the BASCOE 3D-CTM (Theys et al, 2009) and applying these correlations to the local GOME-2 observations of ozone and stratospheric NO 2 columns. They converted the tropospheric slant columns to vertical columns with an air mass factor assuming a Gaussian-shaped vertical distribution of BrO peaking at 6 km altitude.…”
Section: Comparison To Satellite Observations Of Tropospheric Bromentioning
confidence: 99%
“…In a second step, the stratospheric component of the signal is removed by subtracting the stratospheric BrO column, calculated using a stratospheric BrO climatology. The stratospheric BrO correction is based on a dynamical climatology generated from the BASCOE 3D chemical transport model (Theys et al, 2009). This climatology explicitly accounts for the impact of atmospheric dynamics and photochemistry on the stratospheric BrO distribution.…”
Section: Satellite Tropospheric Bro Retrievalmentioning
confidence: 99%